Habitat partitioning by mobile intertidal invertebrates of sandy beaches shifts with the tides. Issue 2 (9th February 2022) - Emery, Kyle A.; Kramer, Valerie R.; Schooler, Nicholas K.; Michaud, Kristen M.; Madden, Jessica R.; Hubbard, David M.; Miller, Robert J.; Dugan, Jenifer E.
Abstract: Coexistence of similar species can be influenced by the intensity of interspecific interactions, which often depends on the availability of limiting resources. Habitat availability varies strongly with tidal phase in many intertidal ecosystems, potentially affecting interspecific interaction strength, particularly for mobile species. Four closely related species of highly mobile intertidal detritivores (talitrid amphipods Megalorchestia californiana, M. corniculata, M. benedicti, M. minor ) inhabit sandy beaches in southern California, where they consume wave‐cast macroalgal wrack originating on coastal reefs. Their coexistence suggests that mechanisms, such as niche separation, are operating to weaken competition among these species. To evaluate this possibility, we explored how tidal phase may mediate temporal and spatial patterns of habitat use among these closely related congeners. We hypothesized that neap tides that reduce intertidal habitat would strengthen temporal separation between species, whereas spatial separation would be greater during spring tides when more habitat is available. We investigated these questions during spring and neap tide phases using (1) comparisons of intertidal distributions of burrowed amphipods and (2) observations of surface activity of amphipods from pitfall traps and mesocosms. We found significant effects of tide phase and species identity on mean intertidal positions and separation of burrowed amphipods. Intertidal distributions of the four species overlapped during neap tide and were significantly separated during spring tide when more intertidal habitat was available. Surface activity patterns differed among species and were more widely separated in time during neap tide than during spring tide. Consequently, the cumulative activity time of all species on neap tides was twice that observed during spring tides. Our findings suggest that mobile intertidal species, like these sympatric talitrid amphipods, can avoid interspecific competition by shifting their activity patterns with tide phase and beach condition. As rising sea levels reduce beach habitat, interspecific competition among these important intertidal consumers may increasingly influence their behavior and coexistence.